Deslocamento geográfico e padrões de uso linguístico: a variação entre as preposições em ~ ni na comunidade de práticas da Universidade Federal de Sergipe - Ribeiro, Cristiane Conceição de Santana (2019)
The public policies of democratization of access to higher education have caused great changes in the scenario of public institutions from all over Brazil. Students from different social profiles were able to attend undergraduate courses through actions such as the Law of Quotas and Sisu, which has led to the migration and mobility of students to university centers, generating social, cultural and linguistic contacts. The situation of contacts can lead to dialectical accommodation, by convergence and divergence, according postulates the Accommodation Theory (GILES; COUPLAND; COUPLAND, 1991). The Federal University of Sergipe (UFS) is a space that allocates these contacts and constitutes a great community of practices, allowing the observation of the dynamics of linguistic change. We select a linguistic trait, the variation between locative prepositions “em ~ ni”. From the linguistic point of view, the variant “em”, according to Castilho (2010), is the result of a paradigmatic morphonemic regularization of in, which would represent a neutral gender, by parallelism to the amalgamated forms “na” and “no”. From the social point of view, previous studies indicate that the variant is associated with rural speaking and less schooling. However, societal evidences point to their non-stigma. Considering the context of contact of the community practices of UFS, we aim to describe the patterns of use of locative prepositions in relation to the accommodation processes associated with the objective and subjective dimensions of the speakers. We start from the point that the variant “ni” occurs in the speech of the sample students and it is not stigmatized in the community. As a method, we performed the sociolinguistic documentation of the community with the recording of 64 interviews with UFS students, stratified as to 4 types of displacements: I Aracaju residents; II residents of the interior of the state that move in the pendular movement towards the University; III born and raised in the interior, but who came to live in the capital because of the University; IV born and raised in other states, but who came to live in Aracaju because of UFS, and the time of course. 3044 occurrences were identified in contexts that allow the variation of the preposition, which were submitted to quantitative treatment regarding the objective and subjective dimensions. In the objective dimension, the results point to 96% of use of the preposition in and only 4% for variant “ni”. Although it is not very frequent, the distribution of occurrences, we observed effect of the displacements: the students of displacements II and III were those that made greater use of variant ni, followed by displacements IV and I. The variable time of course did not show statistically significant difference for use of form “ni”. These results signal the effect of the origin and direction of change, from the interior to the capital, and which is not affected by exposure to the community. The type of argumentative text, more formal, favored the use of the preposition “n” in relation to narrative and dialogue. In relation to the linguistic context, they favor the variant “ni”, the preceding articulating class, the next determining class, and later vowel phonological nature. These results reinforce the hypothesis of origin of the form n as resulting from a paradigmatic process of morphophonemic regularization. For the subjective dimension, we consider the repairs as indirect clues: 4 repair operations were identified with the form “ni” (“no” for “ni”; “ni” for “no”; “em for “ni”; “no” for “ni”). The repair of “ni” for “no” signal morphological adequacy, because it introduces an element that requires gender marking, reinforcing the hypothesis of morphophonemic regularization. Now, the repairs from “no” to “ni” and “em” to “ni” suggest that the variant is integrated to the grammar, without carrying stigma. The obtained results allow to trace the path of linguistic change through which the variant “ni” passes, contributing to the identification of the forces that act in the linguistic and social integration.